(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acute pyelonephritis represents a severe and potentially life-threatening infectious complication in patients with diabetes mellitus. The presence of chronic hyperglycemia alters immune function, disrupts microcirculation, and creates favorable conditions for rapid bacterial proliferation within the urinary tract. As a result, diabetic patients frequently experience a more aggressive disease course, higher rates of complications, and prolonged hospitalization. The present study aimed to comprehensively evaluate the impact of blood glucose levels on the clinical course, complication profile, and treatment outcomes of acute pyelonephritis in hospitalized patients with diabetes mellitus. A retrospective observational analysis was conducted involving 76 adult patients with diabetes mellitus who were treated for acute pyelonephritis at a tertiary care hospital between January and December 2024. Clinical data, laboratory findings, imaging results, and therapeutic interventions were analyzed with particular emphasis on glycemic status and insulin dependence. The results demonstrated that poor glycemic control was strongly associated with increased disease severity, higher incidence of renal abscess formation, and the need for invasive interventions. Insulin-dependent patients exhibited significantly higher blood glucose levels and a greater frequency of complications compared to non–insulin-dependent patients. Optimization of glycemic control during hospitalization was associated with improved clinical outcomes and reduced length of hospital stay. These findings underscore the critical importance of maintaining optimal blood glucose levels in diabetic patients with acute pyelonephritis and highlight glycemic control as a key modifiable factor in reducing complications and improving prognosis.